Sistem Pengelolaan Target Perusahaan dengan Microservices Architecture untuk Membantu Peningkatan Kinerja Perusahaan - Alwan Alyafi Mulyawan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The impact of the Covid-19 pandemic has caused the work pattern at the company to change, should work in the office be shifted to work from home. Therefore, companies need to implement performance management, the aim is to manage employee performance in individuals or teams and use it as information to improve the quality of employees in order to achieve company goals. To achieve this, a target management system is needed that can assist the company in target management. This study aims to develop a target management system using a microservices architecture. By using microservices companies can divide services into small applications that are easy for application scalability